Contextualizing Sanctuary Cities: A Descriptive Analysis into America’s “Most Welcoming Spaces” - Atienza, William (My University, 2023)
Sanctuary cities are jurisdictions that implement various local-level policies limiting cooperation with federal immigration authorities. Inspired by the literature exploring the historical and legal process by which they emerge, this study is motivated to expand this topic into analyzing the descriptive characteristics that contextualize sanctuary cities and compare the places that adopt sanctuary policies opposed those that do not. Building on the group threat literature that explores how racial prejudice manifests into immigration policy, this paper complicates these theoretical assumptions by considering how the combination of demographic characteristics, population opinion, and government structure are associated with sanctuary status. Using a novel comprehensive dataset of contemporary sanctuary cities, the findings produced statistically significant results suggesting that sanctuary cities are situated in a complex relationship of liberal political ideologies, positive population attitudes towards immigrants, and a government structure that is normally incentivized to legislate in favor of progressive policies.
Thesis (Master's)--University of Washington, 2023
Keywords: contexts of reception; group threat; immigration policy; quantitative analysis; Sanctuary Cities; Sociology; Sociology